RADIOGRAPHIC IMAGING OF BIPHASIC SYNOVIAL SARCOMA ON LEFT ELBOW - Firman P, Sitanggang; I Made, Wijaya (Medicina; Vol 43 No 2 (2012): Mei 2012)
Synovial sarcoma is the fourth most common type of sarcoma. It represents between 5% -10% of all soft tissue sarcomas and most prevalent in aged between 15 - 40 years . Synovial sarcoma is the most commonly misdiagnosed soft tissue malignancy, initially as an inflammation process,often because it may be slow-growing, have a benign appearance on imaging studies, may vary in size, and may have pain similar to that associated with trauma.    A rare case is presented of 17 years old women with a synovial sarcoma biphasic. The primary tumor originated in the left elbow since 2004. Since then, the patient has had repeated passive or active left elbow pain and tenderness. No history of trauma. She has not developed metastases of the lung. The patient refused to have surgery and others medical procedures that already planned and explained to her. The conclusion of this case report point that radiology is important to diagnosis and planning for further management
Keywords: synovial biphasic sarcoma, left elbow, radiology imaging